Pluralismo Jurídico: a experiência jurídica na reserva Tapajós - Arapiuns - Lamarão, Josinete Sousa (2010)
The aim of this study is to analyze and reflect, from the community-participatory juridical pluralism, how the “new social movements”, illustrated here by the inhabitants of fourteen communities who live in the “Reserva Extrativista Tapajós-Arapiuns”, located in the region known as “Médio Tapajós”, create and implement their own set of rules in order to answer the group's needs. The juridical backgound of these communities is the formulation of a Settlement Agreement, which was ratified by Pará State Prosecutor Office in 2007, and also with the work of their Communitarian Security Council. Such initiative is seen as an "alternative" way to solve dispute problems among the members of the communities. The minimal presence of the State and the increasing incidence of problems related to Public Security in the communities are cited as the main motivations that encouraged the creation of a Secutiry Council in the the region. Such situations are true expressions of legal pluralism which is presented as a proposal for a new paradigm that should replace the current national legal model characterized by the State Monopoly, where the State is the only entity that creates rights. Despite the fact that there is constitutional recognition of social plurality, there are, on one side, an alternative legal practice under construction by traditional communities, while on the other, the State that, despite the formal recognition of social diversity, has no tradition in dealing with legal pluralism. Keywords: Juridical Pluralism - communitarian-participatory. Social Movements. Normative Paradigms.